2016
DOI: 10.1007/s10067-016-3254-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vascular function in systemic onset juvenile idiopathic arthritis

Abstract: An increased incidence of cardiovascular disease has been found in rheumatic disorders. Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in children. Prolonged immunological inflammatory process leads these patients to an early onset of atherosclerosis. We aimed to assess the presence of early vascular dysfunction in patients with systemic onset juvenile idiopathic arthritis (sJIA) and investigate the role of therapy sJIA in vascular health. Thirty-three patients (22 males, 11 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…19,23 Sozeri et al found that PWV and AIx considered direct and indirect signs of arterial stiffness higher in patients during the active stage of systemic JIA. 24 In our study, we could not detect any difference in the CIMT values of patients during the active disease stage. We believe that this should be further investigated in patient groups during active and remission stages, with more homogeneously disturbed age and disease subgroups.…”
Section: Discussioncontrasting
confidence: 67%
“…19,23 Sozeri et al found that PWV and AIx considered direct and indirect signs of arterial stiffness higher in patients during the active stage of systemic JIA. 24 In our study, we could not detect any difference in the CIMT values of patients during the active disease stage. We believe that this should be further investigated in patient groups during active and remission stages, with more homogeneously disturbed age and disease subgroups.…”
Section: Discussioncontrasting
confidence: 67%
“…Two patients concurrent with sJIA-LD during the MAS phase have been found to have vascular involvements, including cerebral venous sinus thrombosis or coronary artery lesions. Vascular function is impaired in patients with sJIA at a very young age, showing increased arterial stiffness, especially in those presenting with MAS [7] . Vascular endothelial cells are activated by in ammatory cytokines and further contribute to the intravascular coagulation of sJIA.…”
Section: Discussionmentioning
confidence: 99%
“…AS is hypertension independent in patients with chronic kidney disease or inflammatory disease, as shown by AS reduction with anti-TNF-α therapy, without changes in blood pressure levels [163]. AS also appears from a very young age in patients with inflammatory diseases [164]. Vulnerable individuals are at risk of early development of complications usually expected later in life.…”
Section: All About Eva (Early Vascular Aging)mentioning
confidence: 99%